2009
DOI: 10.1159/000241723
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contractile Impairment of Fast- and Slow-Twitch Skeletal Muscles in a Rat Model of Doxorubicin-Induced Congestive Heart Failure

Abstract: Congestive heart failure (CHF) is associated with exercise intolerance that cannot be entirely explained by hypoperfusion of the skeletal muscles. We studied the contractile properties of fast-twitch (extensor digitorum longus; EDL) and slow-twitch (soleus; SOL) skeletal muscles in doxorubicin-induced CHF in rats, and evaluated the defective steps of excitation-contraction coupling. Both types of muscles-obtained from CHF rats displayed significant reduction in twitch and tetanic contractions. Twitch half-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
2
18
1
1
Order By: Relevance
“…However, contraction fall time in HF SOL muscle was higher than in the control group. This finding is in accordance with to Ertunc et al (2009) who showed that HF leads to prolongation of twitch fall time only in SOL muscle. Kuno et al (1988) reported that muscles with higher proportions of type II fibers (fast twitch and glycolytic metabolism) have longer fall times than muscles with a predominance of type I fibers (slow twitch and oxidative metabolism).…”
Section: Discussionsupporting
confidence: 93%
“…However, contraction fall time in HF SOL muscle was higher than in the control group. This finding is in accordance with to Ertunc et al (2009) who showed that HF leads to prolongation of twitch fall time only in SOL muscle. Kuno et al (1988) reported that muscles with higher proportions of type II fibers (fast twitch and glycolytic metabolism) have longer fall times than muscles with a predominance of type I fibers (slow twitch and oxidative metabolism).…”
Section: Discussionsupporting
confidence: 93%
“…Our previous work [6-8], along with others [29, 54, 55], demonstrates skeletal muscle from healthy rodents exposed to doxorubicin show a decrease in muscle strength and an accelerated rate of fatigue. Muscle weakness can result from impaired membrane excitability, calcium release/uptake, and/or myofibrillar protein function.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the data indicate that the nNOS‐mediated effects on contractile function and economy are curtailed in CHF rats. By extension, the muscle contractile dysfunction evident in CHF subjects (Perreault et al 1993; Lunde et al 2002; Ertunc et al 2009) must occur via dysregulation/dysfunction of other mechanisms occurring simultaneous with nNOS downregulation. For example, CHF induces elevated intracellular iNOS, which correlates with exercise intolerance (Hambrecht et al 1999), and impaired sarcoplasmic reticulum function and calcium regulation (Perreault et al 1993; Reiken et al 2003), which likely contribute to contractile dysfunction in CHF.…”
Section: Discussionmentioning
confidence: 99%